DAMPAK KAPITALISASI SEWA OPERASI TERHADAP LAPORAN KEUANGAN DI INDONESIA - Lisa Anggraini (2021)
PSAK 73 is a new accounting standard that introduces a single accounting model for lessees, which records their leasing activities as a capital lease. This study aims to determine the impact of capitalization of operating leases on financial statements. This research is a type of quantitative research using secondary data in the form of annual reports and company financial statements. Objects of this study are companies listed on the Indonesia Stock Exchange 2018-2019 period revealed the value of the future minimum lease payments on operating leases in the financial statements. The empirical model in this study using the constructive capitalization method developed by Imhoff, et al. (1991). Methods of data analysis in this study are descriptive statistical test and Wilcoxon signed-rank test. The results showed that operating lease capitalization has a significant effect on unrecorded lease liability, unrecorded lease assets, equity, and financial ratios. Also, empirical evidence shows that there are tax savings from capitalizing operating leases.